1994
DOI: 10.1111/j.1464-5491.1994.tb02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset Diabetes: Parents' Views

Abstract: During 1990-91 postal questionnaires were sent to the parents of 309 children living in the United Kingdom who developed diabetes before the age of 2 years during 1972-1981. The aim of the survey was to explore how they had coped with their child's condition. Completed questionnaires were returned by 85% of parents. The children had a mean age of 14 (range 9-19) years and diabetes for a mean duration of 13 (range 9-18) years. The cohort's mean age for starting self-injection was reported to be 8 years and most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“…[16][17][18] Studies addressing the effect of time elapsed since the diabetes diagnosis on parental distress have, however, so far reached divergent results. [16][17][18][19][20] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Studies addressing the effect of time elapsed since the diabetes diagnosis on parental distress have, however, so far reached divergent results. [16][17][18][19][20] …”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] Studies addressing the effect of time elapsed since the diabetes diagnosis on parental distress have, however, so far reached divergent results. [16][17][18][19][20] The effect of disease type and of time passed since the child's diagnosis on parental distress was of particular interest in this study, in which the following questions were addressed: What amounts and kinds of disease-related distress are associated with parenting a child through serious and chronic illness? Do parents of children with cancer and diabetes differ from each other regarding level of experienced distress and regarding how subtypes of distress symptoms appear?…”
mentioning
confidence: 99%
“…Parker et al (1994) surveyed the parents of 309 children who were diagnosed with diabetes 10 years prior to the study. They reported that some aspects of daily diabetes management, such as blood and urine monitoring, become less stressful as time passed.…”
Section: Discussionmentioning
confidence: 99%
“…12 A survey of parents in the UK in 1994 found that the mean age for starting self-injection was 8 years. 13 However, a US study of 100 youths with diabetes indicated caution about encouraging maximal self-care autonomy and suggested that families who can succeed in maintaining some parental involvement in diabetes care may have better outcomes. 14 Similarly, a study of 89 youths with diabetes in Germany found continued parental monitoring to be beneficial for glycaemic control as long as a balance was found between medical adaptation to the illness and the child's developmental needs.…”
mentioning
confidence: 99%